Carbon nanomaterials for simultaneous determination of dopamine and uric acid in the presence of ascorbic acid: from one-dimensional to the quasi one-dimensional. (1st February 2016) - Hu, Huifang; Song, Yingpan; Feng, Miao; Zhan, Hongbing
Abstract: The one dimensional (1D) carbon nanomaterials have been conceived as the suitable candidate for the biosensor, but the effect of their structures on the biosensing properties was deficient. Here, we chose carbon nanotubes (CNTs), graphene nanoribbons (GONRs) as models for 1D and quasi 1D carbon nanomaterials, and partially unzipped CNTs (PUCNTs) as an intermediate material, to investigate structure-dependent electrocatalysis of 1D carbon nanomaterials. The 1D to quasi 1D carbon nanomaterials with various surface areas, defect densities and oxygen contents were used to modify the electrodes and exhibited excellent electrocatalytic activities and performances towards UA and DA without the influence of AA. The CNTs with low oxygen and defect content helped to induce direct electron transfer and displayed a highest sensitivity; with abundant oxygen functional groups, the GONRs exhibited a broadest linear detection range; for the intermediate material, PUCNTs showed secondary electrochemical response for UA and DA. Additionally, the 1D carbon materials were applied in the real samples with satisfactory results. The 1D carbon materials demonstrated different electrochemical behaviors and thus can provide rational choices for developing higher sensitivity and wider linear range biosensors by optimizing and controlling the nanostructure.